A Novel Process Chain for the Production of Spherical SLS Polymer Powders with Good Flowability. (2015) - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang
Abstract: Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) applying polymer powder systems is promising. In the case of SLS basically only polyamide is available as an optimized powder material showing satisfying behavior during processing. Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. Within this account we present a novel process route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the process chain is demonstrated for polystyrene (PS) and poly butylene terephthalate (PBT) and the increase of powder flowability after the consecutive process steps has been monitored using a tensile strength tester. The influence of particle habitus and surface functionalization on powder flowability and its properties is discussed. In a first step polymer microparticles are produced by a wet grinding method at reduced temperatures. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns and adapted to specific needs. The dependencies of mean product particle size, particle size distribution and grinding kinetics on stressing conditions, system composition and especially process temperature (increase of the brittleness of the polymer vs. increase of dampening of grinding bead motion with decreasing temperature) will be extensively discussed for the polymers PS, PBT, poly oxo methylene (POM) and Poly ether ether ketone (PEEK). The comminution products obtained typically consist of microparticles of irregular shape and poor powder flowability, i.e. these intermediate products are cohesive and thus will show poor SLS processability. An improvement of flowability of the ground polymer particles is achieved in a second step by changing their shape. The irregular particles are rounded using a heated downer reactor. It will be demonstrated that the 'degree' of rounding can be controlled by changing the temperature profile or the residence time. To further improve the flowability of the cohesive spherical polymer microparticles nanoparticles are adhered to the microparticles' surface in a third step. The improvement of powder flowability after the consecutive process steps is remarkable: rounded and dry-coated PS powders exhibit a strongly reduced tensile strength (by a factor 5) in comparison to the tensile strength of the edged PS comminution product. The improved flowability and packing behavior of the polymer powders open new options in SLS processing including the usage of much smaller polymer beads.